THE ENVIRONMENTAL DAMAGE CAUSED BY THE WASTE PROBLEM IN THE BATANGHARI JAMBI RIVER AFFECT ECONOMIC SUSTAINABILITY? - Sanny Nofrima (TheJournalish: Social and Government, 2022)
This Batang Hari River has an essential role in the Jambi people's lives. Besides the river as a source of public search, the Batang Hari River is also used for the people's daily activities. Uncontrollable garbage dumps due to human activity will impact the beauty of the region, the emergence of the smell of waste decay, air pollution due to the burning of garbage that disrupts public health and becomes a source of disease for human health. There is a habit of people making rivers as a place of garbage dump into waterways. This research aims to study the factors affecting the behavior of people in removing garbage by ethnographic methods. Research with ethnographic approaches in the form of data collection and information through observing the situation that became the object of Research and combining with documentation serving. Research results showing a lack of public understanding of the consequences that can be caused by garbage, lack of government costs to provide/strive for proper waste management and qualify. Therefore, if not handled correctly, it will cause impacts such as water pollution, air, and soil resulting in the source of disease. There is also the relationship between knowledge, education, income, and attitude that affects people's behavior throwing waste.